2001
DOI: 10.1046/j.1528-1157.2001.32800.x
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment Gap in Epilepsy: The Current Situation and Ways Forward

Abstract: Summary:This article is a summary of a workshop held by the ILAE concerning the issue of the epilepsy treatment gap in developing countries. The gap is defined in terms of those people with epilepsy who are not being appropriately treated and is the result of an array of medical, political, social, economic, and cultural factors. The situation regarding the treatment gap for various countries is reviewed, along with some of its causes. Although the overall gap is estimated to be large, a number of recent proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
219
0
21

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(243 citation statements)
references
References 12 publications
3
219
0
21
Order By: Relevance
“…In a systematic review of the TG in DCs, Mbuba et al [50••] observed a high degree of heterogeneity and inconsistency between studies. The overall estimate of the TG was 56%, which is much lower than the 80% to 90% that is widely quoted in many studies [3,49]. The variation in estimates may be explained by nonuniform methods used to estimate the TG as well as the diverse study populations.…”
Section: Treatment Gapmentioning
confidence: 66%
See 2 more Smart Citations
“…In a systematic review of the TG in DCs, Mbuba et al [50••] observed a high degree of heterogeneity and inconsistency between studies. The overall estimate of the TG was 56%, which is much lower than the 80% to 90% that is widely quoted in many studies [3,49]. The variation in estimates may be explained by nonuniform methods used to estimate the TG as well as the diverse study populations.…”
Section: Treatment Gapmentioning
confidence: 66%
“…The TG is defi ned as the number of people with active epilepsy not on treatment or on inadequate treatment; it is expressed as a percentage of the total number with active epilepsy [49]. The gap is reported to be infl uenced by various factors, including lack of access to or knowledge of AEDs, poverty, cultural beliefs, stigma, poor health delivery infrastructure, and shortage of trained professionals [49].…”
Section: Treatment Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has to be acknowledged that more than 80% of people with epilepsy live in developing countries, where the condition remains largely untreated 8 . These people could lead normal lives if properly treated, but the majority of them do not receive any effective treatment [8][9][10] . Because epilepsy is a complex disease, genetic influences as causal factors of the epilepsies can point the way to new treatment strategies.…”
Section: Resumo -Em 12 De Fevereiro De 2009 Nós Comemoramos O Aniversmentioning
confidence: 99%
“…1 In addition, the large majority of people with epilepsy around the world are not under treatment with AEDs, largely because of their lack of access to physicians, the costs of AEDs, and cultural attitudes toward modern treatments. 2 Over thousands of years, people with epilepsy have used a variety of botanicals and herbs, hereafter referred to simply as herbal therapies (although no clinical benefit is implied by this term). Today, herbal therapies are among the most commonly used forms of complementary and alternative medical (CAM) therapies by patients.…”
Section: Introductionmentioning
confidence: 99%